Peran Guru Mata Pelajaran Akidah Akhlak Dalam Menghadapi Era Digital di Madrasah Tsanawiyah Ecellent Zainul Hasan Balung Jember - Fatimah, Siti; Sabiq, Ahmad Fikri (Pendidikan Islam Pascasarjana IAIN Jember, 2024)
This paper aims to determine the improvement of learning outcomes through the Card Sort method on the subjects of the Qur'an Hadith material about the law of Mad reading. This study is a class action research conducted in Class VIII-B MTs Amal Sholeh Getasan, Kab. Semarang. The method of data collection was conducted by interview, documentation, observation and test. This study found that with this card Sort method students can be more enthusiastic and more motivated in learning with proven increase in the percentage of attention so that student learning outcomes also increased. Improvement of learning outcomes is evidenced by the acquisition of the average value of students from cycle I: 20%, Cycle II: 75% and cycle III: 100%. This means that the Card Sort method is very influential on learning the subjects of the Qur'an Hadith material about the law of Mad reading.